PENGARUH HYPNOTHERAPY DAN TINGKAT KECEMASAN TERHADAP KONSENTRASI PADA PERTANDINAGAN BOLA VOLI ATLET PUTRI PPLP-D SUMATERA UTARA (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2018)
The problem in this research is that if the athlete plagued with high anxiety, and decreased concentration cause athletes difficulties in controlling movement, can not implement the strategy because it does not know what to do so that will ultimately affect the appearance, confidence be reduced and even disappear. The purpose of this study is to determine the hypnotherapy effect and anxiety level toward concentration of female athletes PPLP-D, North Sumatra.The research used experimental method with experimental models of 2 x 2 factorial design study. The population are 12 female athletes from PPLP-D, North Sumatra. Sampling technique taken from total sampling. Data collection techniques used Model Gread Concentrasiontest. The data were analyzed using ANOVA byanalysis prerequisite test, normality, and homogeneity. Results of the study: 1) There is no significant difference between the treatment of hypnosis and self-hypnosis to the concentration of female athletes, 2) There is no significant difference between high anxiety level and slightly higher against the concentration of female athletes, 3) There is no interaction between hypnotherapy treatmentand the anxiety level toward concentration of female athletes.The research that was carried out can be concluded that there is reduction inthe level ofanxietyand concentration of athletes who are given hypnosis treatment but not significantly increase which is in 33.33% ofthe hypnosis treatment group and 25% of theself-hypnosis treatment group. It is suggested for the volleyball trainer and coachesto prefer hypnosis in the treatment as the mental training efforts for athletes.Â Keywords: Concentration, Hypnotherapy, Anxiety Level